2018
DOI: 10.1016/j.arth.2017.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Not Physical Activity, but Patient Beliefs and Expectations are Associated With Return to Work After Total Knee Arthroplasty

Abstract: No association between preoperative PA and RTW after TKA was found. Patient beliefs and preoperative expectations did influence RTW and should be addressed to further improve RTW after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 29 publications
(57 reference statements)
2
28
0
Order By: Relevance
“…Preoperative sick leave appears to be a consistent prognostic factor for RTW. All studies that included preoperative sick leave in the analysis found lower RTW for patients who were absent from work preoperatively, which is in line with findings in patients undergoing knee arthroplasty [ 24 , 71 , 72 ]. Furthermore, a higher preoperative workload was associated with lower RTW in most studies.…”
Section: Discussionsupporting
confidence: 79%
“…Preoperative sick leave appears to be a consistent prognostic factor for RTW. All studies that included preoperative sick leave in the analysis found lower RTW for patients who were absent from work preoperatively, which is in line with findings in patients undergoing knee arthroplasty [ 24 , 71 , 72 ]. Furthermore, a higher preoperative workload was associated with lower RTW in most studies.…”
Section: Discussionsupporting
confidence: 79%
“…Also, one could speculate that the activities-of-daily-living and leisure-time goals were not ambitious enough, given the previously reported low metabolic equivalent of task values in our cohort 4 . Finally, it is known that patients’ perception that their knee symptoms are work-related is associated with worse results in terms of return to work after KA 33 . In our study, only in the intervention group, by formulating personal GAS goals, did patients specifically address their most important work-specific activity limitations caused by knee symptoms with their therapist.…”
Section: Discussionmentioning
confidence: 99%
“…Return to work after TKA is influenced by several determinants including state of patient's general health and presence of comorbid diseases, psychosocial and motivational factors, rate of work-related knee demand, and possibility to make adjustments to work tasks. In addition, Hoorntje et al reported that also patient beliefs and preoperative expectations influence return to work after TKA [42]. Predictors of successful return to work after knee replacement have not been thoroughly studied.…”
Section: Discussionmentioning
confidence: 99%